Relationship of Nurse Emphaty to Patient Satisfaction Levels at Puskesmas Burneh - Raufuddin, Raufuddin; Astuti, Enny Tri (Fundamental and Management Nursing Journal, 2020)
Introduction: Patient satisfaction is the patient's response to evaluating the perceived mismatch between initial expectations and perceived actual performance. All patients should feel satisfied with the services they receive. The fact that many patients say they are not satisfied. One of the factors contributing to dissatisfaction is empathy. The purpose of this study was to determine the relationship between nurses and the level of patient satisfaction at the Burneh Health Center, Bangkalan Regency in 2017.Methods: This type of research is an analytic study with a cross sectional design. The study population was 48 patients treated at Burneh Health Center. The sample size was 43 people with a sampling technique using quota sampling. Data collection using a questionnaire. The statistical test in this study used the Spearman Rank test with a significance level of α = 0.05.Results: From the analysis obtained, most (60.5%) or 26 people said that nurses' empathy was not good, (20.9%) or 9 people said that nurses' empathy was good, and (18.6%) or 8 people said that nurses' empathy was very good. good. Most of the patients (67.4%) or 29 people said they were not satisfied, (18.6%) or 8 people said they were satisfied, and (14.0%) or 6 people said they were very satisfied. The Spearman Rank statistical test shows the value of p (0.003) <α (0.05), meaning that H0 is rejected and H1 is accepted. This shows that there is a significant relationship between nurses' empathy and the level of patient satisfaction at Burneh Health Center, Bangkalan Regency in 2017.Conclusion: Nurse empathy is sufficient to influence patient satisfaction. For this reason, nurses are expected to increase their empathy skills, so that patient satisfaction can be achieved as a whole in determining the quality of health services.